La Résilience urbaine : un nouveau concept opérationnel vecteur de durabilité urbaine ? - Marie Toubin; Serge Lhomme; Youssef Diab; Damien Serre; Richard Laganier (Développement Durable et Territoires)
Urban resilience questions the way we think urban systems and disturbances. Applied to cities, resilience is the ability of a city to absorb a disturbance and recover its functions after the disturbance. Then, urban systems need to adapt their functioning and their components to possible disturbances. In managing the crisis and organizing the recovery process, the complexity of urban systems must also be taken into account. Then, it seems that translating the theoretical concept of resilience into practice is possible if functioning, interactions, disturbances and stakeholders are analyzed together, which should contribute to urban sustainability at the same time. Urban services are a relevant case study in doing so. We first review the definitions of both concepts: sustainability and resilience, in order to discuss the conceptual links between them. Then we propose methods and tools dedicated to practioners involved in making cities resilient and sustainable and we discuss the limits of the concepts.